Effect of N2–H2 Ratio during Conventional Plasma Nitriding of Intermetallic FeAl40 Alloy on Electrochemical Corrosion Parameters in Sulphuric Acid - Ngoc Minh Le; Marcel Mandel; Lutz Krüger; Horst Biermann; Anke Dalke (Metals, 2022)
The intermetallic alloy FeAl40 was plasma nitrided at 575 <semantics>∘</semantics>C for 4 h while varying the N<semantics>2</semantics>–H<semantics>2</semantics> gas mixture with nitrogen contents f<semantics>N2</semantics> between 0.1 and 0.9. The effect of the gas mixture on the resulting structure of the nitrided FeAl40 and the associated electrochemical corrosion behaviour in a 0.25 M H<semantics>2</semantics>SO<semantics>4</semantics> (pH = 0.3) electrolyte were investigated using different complementary analytical methods such as scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray spectroscopy, electron probe microanalysis (EPMA), electrochemical polarisation and electrochemical impedance spectroscopy. Nitriding significantly changed the corrosion mechanism of FeAl40 alloys in acidic environments, ranging from consistently high material loss in untreated base material to strongly inhibited material loss. This phenomenon was the result of a corrosion product layer formed on nitrided FeAl40 during the corrosion process. Therefore, plasma nitriding reduced the corrosion rate to about 5–7 mm/year compared with 22 mm/year of the untreated FeAl40 base material. A high nitrogen content in the N<semantics>2</semantics>–H<semantics>2</semantics> plasma of more than f<semantics>N2</semantics> = 0.3 ensured the formation of protective nitrided layers on FeAl40. In addition, an approach to explaining the effect of the nitrided layer on FeAl materials was presented on the basis of thermodynamic considerations.